Post Ugi Gold(I)- and Platinum(II)-Catalyzed Alkyne Activation: Synthesis of Diversely Substituted Fused Azepinones and Pyridinones - Kumar, Amit; Vachhani, Dipak D.; Modha, Sachin G.; Sharma, Sunil K.; Parmar, Virinder S.; Van der Eycken, Erik V. (Synthesis, 2013)
A post-Ugi late-transition-metal-catalyzed intramolecular hydroarylation approach opens a new gateway for the synthesis of diversely substituted pyrrolopyridinones, pyrroloazepinones thiophenoazepinones, azepinoindoles, and azepinobenzothiophenes applying mild reaction conditions. A detailed investigation of the scope of this strategy is discussed.
Keywords: gold; platinum; alkyne; Ugi; azepinone; pyridinone